2022
DOI: 10.3390/jcm11206040
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein(a): Evidence for Role as a Causal Risk Factor in Cardiovascular Disease and Emerging Therapies

Abstract: Lipoprotein(a) (Lp(a)) is an established risk factor for multiple cardiovascular diseases. Several lines of evidence including mechanistic, epidemiologic, and genetic studies support the role of Lp(a) as a causal risk factor for atherosclerotic cardiovascular disease (ASCVD) and aortic stenosis/calcific aortic valve disease (AS/CAVD). Limited therapies currently exist for the management of risk associated with elevated Lp(a), but several targeted therapies are currently in various stages of clinical developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 110 publications
0
10
0
Order By: Relevance
“…These oxidized phospholipids stimulate the production of the inflammatory proteins interleukin‐8 and monocyte chemoattractant proteins. Recent research also reveals that the pathophysiology of Lp(a) depends on this pro‐inflammatory impact 35–37 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These oxidized phospholipids stimulate the production of the inflammatory proteins interleukin‐8 and monocyte chemoattractant proteins. Recent research also reveals that the pathophysiology of Lp(a) depends on this pro‐inflammatory impact 35–37 …”
Section: Discussionmentioning
confidence: 99%
“…Recent research also reveals that the pathophysiology of Lp(a) depends on this pro-inflammatory impact. [35][36][37] Regarding Lp(a) inversed relationship with AF, as Tao et al 31 suggested in a large-scale retrospective cohort study indicated that Lp(a) level lower than 32.42 mg/dL could be a potential risk factor for AF. It was interesting to note that only women showed this association.…”
Section: Referencesmentioning
confidence: 99%
“…Apo(a) inhibits tissue plasminogen activator (tPA) activation of plasminogen to plasmin and plasminogen binding to fibrin but also promotes increased platelet activity. Hence it leads to thrombosis [20]. Lp(a) is positively correlated with platelet aggregation independent of lipoprotein-associated phospholipase A2 (Lp-PLA2), which may be partly responsible for the atherothrombotic effect of Lp(a).…”
Section: Pathogenicity Of Lp(a)mentioning
confidence: 99%
“…Lipoprotein(a) (Lp[a]) is a lipid-carrying particle composed of an LDL-like particle containing apolipoprotein B-100 linked by a disulfide bond to apolipoprotein(a). 8 Lp(a) levels are fundamentally determined by genetic variability at the LPA locus. 9 Genetic and epidemiologic studies have shown that high levels of Lp(a) are an independent risk factor for atherosclerotic cardiovascular disease and aortic valve stenosis through mechanisms associated with increased atherogenesis, inflammation, and thrombosis.…”
Section: Introductionmentioning
confidence: 99%